Mitochondrial DNA sequence of the horseshoe crab Tachypleus gigas. Issue 6 (3rd June 2021) - Sarmiento, Maria E.; Chin, Kai Ling; Lau, Nyok Sean; Aziah, Ismail; Norazmi, Mohd Nor; Acosta, Armando; Ismail, Noraznawati; Yaacob, Nik Soriani
Abstract: This paper reports on the complete mitochondrial (mt) genome of a horseshoe crab, Tachypleus gigas ( T. gigas ), in Kuala Kemaman, Terengganu, Malaysia. Whole-genome sequencing of hemocyte DNA was performed with Illumina HiSeq system and the generated reads were de novo assembled with ABySS 2.1.5 and reassembled using mitoZ against Carcinoscorpius rotundicauda and Limulus polyphemus, resulting in a contig of 15 Kb. Phylogenetic analysis of the assembled mt genome suggests that the Tachypleus gigas is closely related to Tachypleus tridentatus than to Carcinoscorpius rotundicauda.